CESifo World Economic Survey August 2011 - Johanna Plenk; Gernot Nerb; Klaus Abberger; Teresa Buchen (CESifo World Economic Survey, 2011)
World Economic Climate: World Economic Climate deteriorates - Economic Expectations: Economic Expectations further downgraded but still positive - Inflation: Inflation pressure remains high despite some softening - Currencies: Yen and euro are seen as somewhat overvalued - Interest Rates: Fewer WES experts expect further increase of short- and long-term interest rates - Special Topic: How should the G20 prioritize selected policy issues during their next summit?
Keywords: 330; World Economic Survey; World Economic Climate; Economic Expectations; Inflation; Currencies; Interest Rates; Special Topic